Extreme weight control behaviors among adolescent athletes: Links with weight-related maltreatment from parents and coaches and sport ethic norms - Boudreault, V.; Gagnon-Girouard, M.-P.; Carbonneau, N.; Labossiére, S.; Bégin, C.; Parent, S. (International Review for the Sociology of Sport, 2022)
The use of extreme weight-control behaviors is prevalent among adolescent athletes and may result from individual and sport-specific factors. Weight-related maltreatment from coaches and parents, and conformity to sport ethic norms have recently been linked to the use of extreme weight-control behaviors. This study aims to investigate the role of sport ethic norms and weight-related maltreatment from coaches and parents in the use of extreme weight-control behaviors among adolescent athletes. A sample of 999 French-Canadian athletes aged 14-17 years competing in a variety of sports completed an online survey assessing extreme weight-control behaviors, weight-related maltreatment from coaches and parents, and conformity to sport ethic norms. A total of 16.9% of the adolescent athletes reported having adopted extreme weight-control behaviors during their athletic careers. Extreme weight-control behaviors were significantly more prevalent among girls (19.75% vs 9.7% in boys) and weight-class-sport athletes (44%). In addition, 7.4% of the sample experienced at least one type of weight-related maltreatment by coaches or parents. Sex, weight-related neglect by coaches and parents, and weight-related psychological violence by coaches explained 24.4% of extreme weight-control behaviors variance. Indeed, participants who engaged in extreme weight-control behaviors experienced significantly more violence than the other participants did. In contrast, no differences were observed between people who engaged in extreme weight-control behaviors and those who did not due to conformity to sport ethic norms.